Evaluation of the curvature ductility ratio of a circular cross-section of concrete reinforced with GFRP bars - Pichardo, C. (2020)
The present study deals with the use of fiberglass reinforced polymer bars (GFRP) as a replacement for the common steel of a reinforced concrete circular pile, in order to avoid the corrosion of durability of reinforcing bars and thus improve them. The comparative analysis was carried out between a pile reinforced with GFRP and another with steel, where the ductility was evaluated by obtaining moment-curvature diagram. As a result, said idealized moment-curvature diagrams and ductility indices are presented, concluding the ductility of the section reinforced with GFRP in 20% more than that of steel.